Ein municipaler Quaestor von Celeia im mittleren Murtal: Die Grabinschrift vom Kirchberg bei Deutschfeistritz, Steiermark - Ehrenreich, Sigrid; Fuchs, Gerald; Wedenig, Reinhold (Arheološki vestnik, 2006)
A Roman tombstone inscription came to light in 2004 in achurch near Deutschfeistritz in the Mur valley about 20 kmnorthwest of Graz. It had been fragmented and partly dam-aged in the course of secondary use as a building element. Thebeginning of the text is not preserved. One of the family mem-bers to be commemorated was a previously unknown munic-ipal quaestor from Celeia. Due to its dimensions, the marblepiece once must have been part of a monumental tomb struc-ture. The site of the tomb is unidentified but it certainly be-longed to the administrative area of Flavia Solva. The archae-ological surroundings contain several remains from the Ro-man period, e.g. two milestones and a whole series of settle-ment remains.